Physiological and Molecular Processes Associated with Long Duration of ABA Treatment - Wang, Mei; Lee, Juhun; Choi, Bongsoo; Park, Youngmin; Sim, Hee-Jung; Kim, Hyeran; Hwang, Inhwan (Frontiers in Plant Science, 2018)
Plants need to respond to various environmental stresses such as abiotic stress for proper development and growth. The responses to abiotic stress can be biochemically demanding, resulting in a trade-off that negatively affects plant growth and development. Thus, plant stress responses must be fine-tuned depending on the stress severity and duration. Abscisic acid, a phytohormone, plays a key role in responses to abiotic stress. Here, we investigated time-dependent physiological and molecular responses to long-term ABA treatment in Arabidopsis as an approach to gain insight into the plant responses to long-term abiotic stress. Upon ABA treatment, the amount of cellular ABA increased to higher levels, reaching to a peak at 24 h after treatment (HAT), and then gradually decreased with time whereas ABA-GE was maintained at lower levels until 24 HAT and then abruptly increased to higher levels at 48 HAT followed by a gradual decline at later time points. Many genes involved in dehydration stress responses, ABA metabolism, chloroplast biogenesis, and chlorophyll degradation were strongly expressed at early time points with a peak at 24 or 48 HAT followed by gradual decreases in induction fold or even suppression at later time points. At the physiological level, long-term ABA treatment caused leaf yellowing, reduced chlorophyll levels, and inhibited chloroplast division in addition to the growth suppression whereas short-term ABA treatment did not affect chlorophyll levels. Our results indicate that the duration of ABA treatment is a crucial factor in determining the mode of ABA-mediated signaling and plant responses: active mobilization of cellular resources at early time points and suppressive responses at later time points.